The Moderating Effect of Halal Traceability System on Halal Food Supply Chain Management and Halal Integrity Assurance Relationship - Mohamed, Yusaini Hisham Bin; Rahim, Abd Rahman Abd; Ma’aram, Azanizawati; Nordin, Mohd Norazmi bin (The journal of contemporary issues in business and government, 2021)
Purpose: The main purpose of this study is to empirically investigate the effect of halal food supply chain management on halal integrity assurance with moderating variable of halal traceability system. Design/ methodology/ approach: This study employed a quantitative research approach, in which survey questionnaires were distributed to 475 Malaysian halal food and beverages companies. A moderated hierarchical regression technique was applied to examine the moderating effect of the hypotheses. Findings: The results revealed that halal traceability system was found to moderate the halal food supply chain management and halal integrity assurance. Halal traceability system had also been found to significantly moderate the supply chain logistics control and supply chain resources on halal integrity assurance relationships. Research Limitations/ Implication: This study focuses on the halal industry in Malaysia specifically for food and beverages producers, its findings cannot be generalized to other business categories. Issues of applicability of this study to other countries also need to be considered. Practical Implication: This study addresses the assurance of halal integrity as a crucial element in managing a halal food supply chain in halal food industry. It has empirically identified the moderating role of halal traceability system to strengthen the halal food supply chain integrity assurance in halal food industry. Social Implications: The study has successfully filled the gap in literature by empirically establishing the moderating role of halal traceability system on halal food supply chain integrity assurance. This result has presented a better understanding of halal integrity assurance concept application in society. Originality/Value: This study is one of very few studies which have empirically link halal traceability system, halal integrity assurance and halal food supply chain management in the halal food industry. The paper’s primary contribution is the finding support to the integration of halal integrity context as an important determinant in present halal food supply chain model in accordance with Islamic requirements.